The differences in Hg content released from high copper amalgam and silverfil argentum restoration into artificial saliva after one week of soaking (in vitro) - Wisuardy, Deriz Rieskanoerbachra; Sukartini, Endang; Armilia, Milly (Universitas Padjadjaran, 2008)
Dental restoration is a treatment in dentistry that very often implemented. One of the restoration materials used is an amalgam. Amalgam has some deficiencies, among others, the presence of free Hg. The purpose of this study was to find out the difference in Hg content released from two different kinds of amalgam, namely, high copper amalgam and silverfil argentum carried out in vitro. This study was carried out on thirty premolar teeth of the maxilla which underwent class one occlusal restoration. The Hg content released was measured using the Atomic Absorption Spectrophotometry (AAS). This was a quasi-experimental study. The study results analyzed using the independent t paired statistical test method indicated that after one week of immersion, the average Hg content released from high copper amalgam restoration was 10,695 ng/mL and from silverfil argentum restoration was 5,602 ng/mL. The conclusion of the study was that there was a difference in Hg content released from high copper amalgam restoration and silverfil argentum restoration. The Hg content released from high copper amalgam restoration was higher than the Hg content released from silverfil argentum restoration.